Climate change, community response, and resilience : insight for socio-ecological sustainability - Chatterjee, Uday; Shaw, Rajib; Bhunia, Gouri Sankar; Setiawati, Martiwi Diah; Banerjee, Soumita (Developments in weather and climate science, 2023)
"Climate Change, Community Response, and Resilience: Insight for Socio-Ecological Sustainability, Volume Six presents a fundamental theoretical framework for understanding how community resilience and risk assessment affect climate change adaptation behavior. This framework is based on a 26-chapter theoretical and empirical examination that includes pioneer projects from various regions that illustrate the relationship between theory and practice, reflect a paradigm shift in climate change, community response, and resilience, and focus on these important aspects from a sectoral perspective. Climate change, ecological consequences and resilience are then discussed in the final section"--